Innovative culture and professional skills: The use of supportive leadership and individual power distance orientation in IT industry. Issue 2 (2nd May 2017) - Yu, Pei-Li
Abstract : Purpose: The point of divergence for the authors' analysis is the observation that research on the development of professional skills did not provide empirical support to a possible positive relationship between innovative culture and development of professional skills. The author believes that the injection of intervening variables has the potential to do just that. The purpose of this paper is to understand such contingencies through a developed moderated mediation model, which jointly examines supportive leadership as the mediating mechanism and individual power distance orientation as a moderator and to increase the theoretical validity and precision of investigating the development of professional skills. Design/methodology/approach: The survey data were collected from 317 information technology (IT) professional technical engineers and their supervisors from high-tech sectors. The authors tested the hypotheses by hierarchical regression and followed Baron and Kenny (1986) instruction to examine our moderated mediation model. The authors used a series of confirmatory factor analyses (CFAs) to verify the constructs' distinctiveness before testing the hypotheses was performed. Meanwhile, in order to test the mediating effect, the three-equation approach to testing mediation, as recommended by Baron and Kenny (1986), was used. Findings: The strong support for schema theory in this study suggests that the development of professional skills can be notably promoted through a moderated mediation model which integrates the link between innovative culture and professional skills through the mediating effect of supportive leadership and the direct effects are mitigated by the moderating effect of individual power distance orientation. It highlights the importance of appropriately matching innovative culture and supportive leadership with the power distance orientation of employees. This universalistic organizational behavior approach has worked effectively in an Asian sample. Originality/value: This study provides a better understanding of work motivation by showing that an employee uses schemas to interpret the relationships among perceived innovative culture, individual power distance orientation, supportive leadership and development of professional skills. This paper also illustrates how perceived innovative culture can act as an positive motivator to inspire IT technical engineers' development of professional skills, and how individually held power distance orientation may positively or negatively influence the relationship between perceived innovative culture and supportive leadership. Hence, this study has extended the schema theory in organizations and informed the literature on supportive leadership.